Implementasi Service Strategy ITIL V3 Pada Sektor Perbankan di Indonesia - Salim, Jodie; Onggie, Karen; Garcia, Kelvin (JDMIS: Journal of Data Mining and Information Systems, 2024)
Companies that develops in technology are that operates in the banking sector. The banking companies used to compare the service strategy are Bank Bapas 69, Bank XYZ, and Bank Mandiri Taspen. The research was carried out by using data collection methods based on literature studies and analyzing them based on ITIL guidelines regarding service strategy. Bank Bapas has used the ITIL V3 framework with a service strategy domain, while XYZ Bank has conducted an evaluation using the ITIL V3 framework with service transition and service operation domain, and Bank Mandiri has used stages in service strategy, namely IT service portfolio, in its development. The results at Bank Bapas reveal that the services used are good and only need periodic maintenance, while at Bank XYZ it shows that IT has been implemented properly and refers to clear and actual procedures, while at Bank Mandiri the output obtained would result in a catalog IT service using service charter for the logistics. The results of the comparison between three journals prove that only a few differences are found, because in the use of service strategy, the majority output is the same in solving problems in the company.